Atomic Structure Teaching Module with PhET Simulation to Increase Student Motivation and Learning Outcomes - Sa’diyah, Alimathus; Lutfi, Achmad (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study aims to obtain the feasibility of teaching modules with PhET simulations to increase student motivation and learning outcomes in atomic structure content as a learning tool. The eligibility of teaching modules consists of valid, practical, and effective criteria. This development research uses the ADDIE research model which consists of five stages which include analysis, design, development, implementation, and evaluation. The trial design used was the One Group Pretest-Posttest Design. The subjects in this study were students of class X SMA Intensif Taruna Pembangunan Surabaya with a total of 30 students. The research instruments used included validation sheets, student response sheets, student activity observation sheets, learning motivation sheets and pretest-posttest sheets. Analysis of the data used using the validity test, analysis of the percentage of practicality and the percentage of effectiveness. The results of the validity test obtained a validation mode score of 4 so can be stated that the teaching modules developed are included in the good category. The results of the practicality test obtained the percentage of students’ response results of 82.3% so can be stated that the teaching modules developed are categorized as very practical. Then the percentage of the effectiveness of motivation to learn before treatment obtained results of 50.6% and after treatment of 85.7%. Based on these percentages, it can be stated that the teaching modules created can increase students’ learning motivation. The learning outcomes of students obtained an N-Gain score of 0.71 which means that the teaching module is in the high category.